The terminology conflict on efficacy and effectiveness in healthcare - Porzsolt, Franz; Wiedemann, Felicitas; Phlippen, Meret Sophie; Weiß, Christel; Weiß, Manfred; Schmaling, Karen; Kaplan, Robert M. (Journal of Comparative Effectiveness Research, 2020)
Designers and architects created the rule ‘form follows function (FFF)’ for their own profession. Our paper demonstrates that this FFF rule applies equally well to the designers of clinical studies. Four examples present are as follows: disregarding this FFF rule causes an inconsistent terminology to differentiate between efficacy and effectiveness, inconsistent differentiation of efficacy and effectiveness interferes with the consistent interpretation of the results of clinical studies, inconsistent interpretation of clinical studies results in an unexpectedly variance of recommendations in clinical guidelines and the fusion of the FFF designer rule and of the demands of Cochrane and Bradford Hill (‘can it work?’, ‘does it work?’ and ‘is it worth it?’) avoids the terminology problem and its misleading consequences. This strategy is presented.